Evaluation of Pomegranate Peel as Bioadsorbent for the Removal of Lead Ions from Aqueous Solutions Using Phytoadsorption Technique - Sharif, Salaheddin A.; Ansir, Najwa H.; Eldagharye, Rehab N. F. M.; Boshaala, Hend Abd Almenam; Kikhia, Fatma M.; Algaddafi, Alia M. A.; Tarhoni, Ahmed S. (Scientific Journal for Faculty of Science-Sirte University, 2024)
Removal of toxic heavy metals from ecosystems is a challenge. Looking for green solutions is always required. Phytoremediation is one of the most powerful, efficient, and sustainable methods. However, phytoadsorption approach was emerged in the last two decades as a potential, cheap, and benign method for the clean up of contaminated aquatic systems from heavy metals. We have investigated the potential of dry pomegranate peels as biosorbent to remove lead ions from their aqueous solutions using the phytoadsorption technique. Different amounts of the dead biomass (5.0, 2.0, and 0.5 g) at varied shaking rates of 400, 600, 800 OSC/min and three periods of contact time were applied. The resulting observations of all experiments showed that the dry pomegranate peels were able to remove up 91.1% of Pb2+ ions from their 1000-ppm aqueous solutions at room temperature and neutral pH. In addition, the pomegranate peel as a bioadsorbent has showed an adsorption capacity up to 96.1 mg/g. Consequently, the pomegranate peels can be used as potential bioadsorbents for the removal of lead heavy metal from the contaminated aquatic systems.